2018
DOI: 10.1007/s10404-018-2124-7
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and clogging phenomena of rigid microparticles in microfluidics

Abstract: We developed a numerical tool to investigate the phenomena of aggregation and clogging of rigid microparticles suspended in a Newtonian fluid transported through a straight microchannel. In a first step, we implement a time-dependent one-way coupling Discrete Element Method (DEM) technique to simulate the movement and effect of adhesion on rigid microparticles in two- and three-dimensional computational domains. The Johnson–Kendall–Roberts (JKR) theory of adhesion is applied to investigate the contact mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This phenomenon was also de scribed by Johansen and Schaefer [33]. According to Shahzad et al [34], particle aggrega tion increases the risks of channel clogging in monolithic columns and reduces the life span of the monoliths. Aggregation is a dynamic process influenced by both intramolec ular and electrostatic forces which lead to the particle-particle interaction eventually forming a compact structure in a pattern [33].…”
Section: Effect Of Surfactant Concentrationmentioning
confidence: 77%
“…This phenomenon was also de scribed by Johansen and Schaefer [33]. According to Shahzad et al [34], particle aggrega tion increases the risks of channel clogging in monolithic columns and reduces the life span of the monoliths. Aggregation is a dynamic process influenced by both intramolec ular and electrostatic forces which lead to the particle-particle interaction eventually forming a compact structure in a pattern [33].…”
Section: Effect Of Surfactant Concentrationmentioning
confidence: 77%
“…Nevertheless, we retain that single microrobots can spontaneously aggregate without peculiar configurations in contaminated water solutions, thus partially reducing the surface area available and making it difficult to understand the different performances between single or aggregated systems. 62 Regarding the use of H 2 O 2 , previous research has demonstrated that the concentrations of 1% H 2 O 2 decreased from 10 000 ppm to less than 2 ppm after 24 h long treatment with hematite microrobots, which is lower than 8 ppm, the allowed limit of H 2 O 2 in drinking water. Consequently, it can be concluded that H 2 O 2 does not introduce new pollution to the water system.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, in the GlF systems, possible clogging can be obtained which can be avoided with the employment of liquid-liquid flow reactors. 67 The microfluidic industrial scale-up technologies offer the opportunity for the fabrication on a large scale of NP-based systems widely used for cancer treatments. 68 The highthroughput fabrication of NPs with control of physicochemical properties such as size and shape is one of the critical points for their effective biomedical applications.…”
Section: Microfluidic Systems Based On Multiphase Flowmentioning
confidence: 99%